A Photovoltaic Charger Suitable for Brain Computer Interface Equipment. Issue 1 (1st April 2022) - Gu, Yifeng; Li, Hao; Zhao, Jiale; Ma, Xiaolin
Abstract: Nowadays, traditional energy is drying up and environmental pollution is increasing. In order to implement the development requirements of energy saving and environmental protection, an efficient and portable photovoltaic charger is designed in this paper with brain computer interface devices as the research object On the hardware side the device is designed with a Boost circuit as the main circuit and on the software side a maximum power point tracking technique with conductance increment method as the control algorithm. Based on the final physical test results, it has been shown that the charger meets the requirements.